Influence of gender, drop handlebar height, and handgrip position on dynamic motion during cycling - Teo, Wee Ting (2015)
Road bicycle cyclists often have saddle discomfort and hand numbness after a long distance and high speed cycling. Fitting for road bicycle cyclist is unique, as it should take different handgrip positions into consideration. Gender difference in pelvic geometry and seat bone width should also take into consideration when designing female road bicycle. In report, cycling motion and pressure distribution was collected in experiment to investigate the gender difference on different handgrip positions and handlebar heights. Result by using manually measured static fit and by using dynamic fit was compared to determine the reliability of manually measured static fit. The dynamic cycling movement showed that males have more stable and periodic cycling movement compare to females. Cyclists with triathlons experience tend to bend more to lower air resistance with narrower shoulder angle. When handgrip position shifted from drops to hoods to tops, both males saddle and hand maximum pressure increased. However, females with larger seat bone width would exert significant high hand pressure at tops to adjust backward the sit location on saddle, when sitting on COBB V Flow saddle, which has a narrow saddle width (V-Flow). The saddle maximum pressure of females fluctuated. When handlebar height shifted from original height H to 5cm increment and 5cm decrement, both hand and saddle maximum pressure increased and resulted in a discomfort riding. Flexibility of participants would affect the pressure result at different handlebar height. With manually measured static fit, 5 out of 10 participants initial back angle was out of desired range, which is 40° to 50°. With dynamic fit, all 8 of participants initial back angle was adjusted within 43.2° to 44.3°, with only 1.1° of difference. It was proved that manually measured static fit was good enough for leisure and normal sports uses; dynamic fit was required for cyclist who have high performance requirement.